2008
DOI: 10.1007/s15010-008-7319-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutical Aspects and Outcome of HIV/HCV Coinfected Patients Treated with Pegylated Interferon plus Ribavirin in an Italian Cohort

Abstract: Although factors such as HCV viral load rates and genotype 1 have been confirmed to threaten the response to therapy, we observed a significant response rate when patients had a history of CD4+ T-lymphocyte nadir >350 per mm3. The high dropout rates due to voluntary discontinuations complicated the patients' case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The double infection is rather frequent, due to common routes of transmission [2,35-37], and liver disease is the second leading cause of death in patients infected by HIV [38]. …”
Section: Discussionmentioning
confidence: 99%
“…The double infection is rather frequent, due to common routes of transmission [2,35-37], and liver disease is the second leading cause of death in patients infected by HIV [38]. …”
Section: Discussionmentioning
confidence: 99%
“…In HIV/HCV co-infected patients, results obtained with PEG-IFN + ribavirin (RBV) [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] were superior to those with PEG-IFN alone, standard IFN alone [48] , or standard IFN + RBV (Table 2). A meta-analyses of 6 randomized controlled studies showed superior sustained virologic response (SVR) with PEG-IFN + RBV compared with IFN + RBV and PEG-IFN monotherapy.…”
Section: Therapeutic Regimen For Treating Hcvmentioning
confidence: 99%
“…Pérez-Olmeda et al [39] Cargnel et al [40] ( Laguno et al [42] ( Myers et al [43] ( Chung et al [44] ( Moreno et al [45] ( Torriani et al [46] ( [49] Moreno et al [50] ( Voigt et al [52] ( Fuster et al [53] ( Righi et al [54] ( Responses are on intent to treat analysis. ETR: End of treatment response (HCVRNA < 50 copies/mL); SVR: Sustained virologic response (HCVRNA < 50 copies/mL 6 mo after discontinuing treatment); PEG-IFN: Pegylated interferon; RBV-ribavirin; GT: Genotype; tiw: Three times a week; ACTG: AIDS clinical trial group; APRICOT: AIDS pegasys ribavirin international coinfection trial.…”
Section: Etr Svr Etr Svr Etr Svrmentioning
confidence: 99%
“…A particularly encouraging result was that the pegylated interferon and ribavirin combination achieved an SVR in 27-44% of coinfected patients [8][9][10][11], resulting in histopathological improvement in most of them. Recent results report similar SVR rates in coinfected more than in HCV mono-infected patients [12][13][14][15]. HCV treatment, however, is given to a small number of HIV-HCV coinfected patients for many reasons, e.g., HCV treatment deemed questionable (minimal hepatic lesions, alcohol abuse, active drug use), lack of available liver biopsy, psychiatric contraindication, and physicians' conviction of poor patient compliance [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%